Determination of tungsten and molybdenum concentrations from an x-ray range spectrum in JET with the ITER-like wall configuration. (28th May 2015) - Nakano, T; Shumack, A E; Maggi, C F; Reinke, M; Lawson, K D; Coffey, I; Pütterich, T; Brezinsek, S; Lipschultz, B; Matthews, G F; Chernyshova, M; Jakubowska, K; et al.
Abstract: The and 3p–4d inner shell excitation lines in addition to 2p–3s lines have been identified from the spectrum taken by an upgraded high-resolution x-ray spectrometer. It is found from analysis of the absolute intensities of the and lines that W and Mo concentrations are in the range of and, respectively, with a ratio of ∼5% in JET with the ITER-like wall configuration for ELMy H-mode plasmas with a plasma current of 2.0–2.5 MA, a toroidal magnetic field of 2.7 T and a neutral beam injection power of 14–18 MW. For the purpose of checking self-consistency, it is confirmed that the W concentration determined from the line is in agreement with that from the line within 20% and that the plasma effective charge determined from the continuum of the first order reflection spectrum is also in agreement with that from the second order within 50%. Further, the determined plasma effective charge is in agreement with that determined from a visible spectroscopy, confirming that the sensitivity of the x-ray spectrometer is valid and that the W and the Mo concentrations are also likely to be valid.